A study of commercial arbitral awards and their legal implications in Saudi Arabia - Althubyani, Bandar Khalid (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
Arbitration is an alternative dispute resolution for seeking justice in settling commercial disputes out of courts. Although the Saudi Arbitration Law of 2012 marked a significant evolution in commercial arbitration in the Kingdom of Saudi Arabia, the current position of setting aside an arbitral award may result in its enforcement with the presence of substantial reasons affecting the justice between the disputants due to the limitation of the grounds for setting it aside. In addition, enforcement of the arbitral award is subject to its consistency with Shariah and the national public policy of the Kingdom of Saudi Arabia. This is seen as legal restrictions for foreign arbitral awards, and it amounts to difficulties in seeking their enforcement. Furthermore, the decision on accepting or refusing the enforcement of the arbitral award is based on the ijtihad (independent reasoning) of the enforcing judge. This study, therefore, analyses the rules concerning the process of setting aside and enforcing the arbitral award. For this purpose, the methodology adopted in this study comprises of non-empirical qualitative and empirical qualitative research. The black letter laws were also employed to evaluate the current situation of the problem by examining the relevant legal rules along with Shariah. This study finds that the grounds for setting aside did not include all the situations that result in setting aside the arbitral award. Moreover, the arbitral award seeking enforcement may be refused due to its conflict with Shariah even though there are other Islamic jurisprudential opinions that consider this award to be in consistence with the Shariah. Thus, the study suggests some necessary amendments of the Saudi Arbitration Law 2012 in order to achieve the desired justice for parties in commercial arbitration.